Attrition among HIV positive children enrolled under integrated HIV care programme in Myanmar: 12 years cohort analysis. Issue 1 (1st January 2018) - Minn, Aung Chan; Kyaw, Nang Thu Thu; Aung, Thet Ko; Mon, Ohn Mar; Htun, Thurain; Oo, Myo Minn; Moe, July; Mon, Aye Aye; Satyanarayana, Srinath; Oo, Htun Nyunt
ABSTRACT: Background : In Myanmar, HIV seropositive children are being enrolled in an integrated HIV care (IHC) Program for HIV treatment and care since 2005. Objectives : To assess the: (a) attrition (death or loss-to-follow-up) rates among children (aged ≥ 18 months to < 15 years) enrolled into the programme before and after initiation of anti-retroviral therapy (ART) (pre-ART and ART periods); (b) demographic and clinical factors associated with attrition during these two periods. Methods : Children enrolled in IHC Programme and their status (death, lost to follow-up, regular follow-up or transferred out) was assessed as on 30 June 2017. Attrition rates (per 100 person-years) at pre – ART and ART periods were calculated and the association between demographic and clinical characteristics with attrition was assessed using Cox proportional hazards model. Results : Among 2, 736 children enrolled, pre-ART attrition rate was 19 per 100 person-years of follow-up (95% CI: 17–21) and ART attrition rate was 4 per 100 person-years of follow-up (95% CI: 3–4) with higher levels during the initial few months of enrolment. The 36-month retention rates during pre-ART period was 75% (95% CI: 72–78) and during ART period was 87% (95% CI: 86–88). The children 'at enrolment' with relatively lower levels of haemoglobin, immune deficiency, underweight for age, higher WHO clinical stages, presence of hepatitis B infection had higher hazards of attrition in both periods. Conclusion : The attrition rates are high particularly among children with relatively poorer clinical, nutritional profiles at enrolment. The study suggests the urgent need for improving adherence counselling especially during the initial few months of enrolment and early ART initiation.